Dispensation of Pre-Marital Pregnancy Marriage in Parigi Religious Court - Madsaid; Lukman S. Thahir; Nasaruddin, Nasaruddin; Hamiyuddin, Hamiyuddin (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2024)
This study discusses the form and factors of implementing the dispensation of premarital pregnancy at the Parigi Religious Court according to Law Number 16 of 2019 and a review of the maqashid shari'ah. The type of research used in this study is qualitative research (field) with a case study approach. The data used in the study are primary and secondary data. Data collection techniques are observation, interviews, and documentation. The results of this study indicate that the form and factors of the implementation of the dispensation of premarital pregnancy at the Parigi Religious Court according to Law Number 16 of 201219 are that every year, the Parigi Religious Court decides and resolves cases of marriage dispensation applications with an average percentage of 93% of prospective brides who are already pregnant outside of marriage have been granted by the judge. The factors for the judge to grant the dispensation of premarital pregnancy at the Parigi Religious Court are formal legal considerations, Supreme Court Regulations Number 5 of 2019 concerning Guidelines for Adjudicating Applications for Marriage Dispensation, as well as material legal considerations, marriage law, ushul fiqh principles, maslahah mursalah, and social justice. The review of maqasid sharia on the form and factors of implementing the dispensation of premarital pregnancy according to Law Number 16 of 2019 is that it does not conflict with Islamic law; in fact, the policy is in line with the objectives of Islamic law (maqasid shari'ah). For now, the author agrees with the consideration of granting the dispensation of premarital pregnancy. Still, the role of maqasid shari'ah only contributes a little, namely considerations related to protecting offspring (hifz al nasal).